(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article discusses the impact of universal processes associated with universal technologies as a result of economic globalization, the acceleration and intensification of the flow of information, on the spirituality of young people. The scientific basis is given to the fact that young people have access to a number of necessary and unnecessary information through various media, especially the Internet, their interest in some of them, their own analysis, and their negative consequences. Also, issues related to protecting young people from information attacks in the conditions of economic globalization are discussed.